Differential expression of aldolase, alpha tubulin and thioredoxin peroxidase in peripheral blood mononuclear cells from dengue fever and dengue hemorrhagic fever patients - Thayan, R.; Huat, T.L.; See, L.L.C.; Khairullah, N.S.; Yusof, R.; Devi, S. (2009)
We determined the differential expression levels of proteins in peripheral blood mononuclear cells of patients with dengue fever (DF) and dengue hemorrhagic fever (DHF). Proteins were subjected to two-dimensional electrophoresis, mass spectrometry and Western blot analysis. We identified 8 proteins that were 2-fold or more LIP-regulated in patients compared to healthy control, three of which, aldolase, thioredoxin peroxidase and alpha tubulin, were related to dengue infection. Both thioredoxin peroxidase and alpha tubulin were over-expressed 4.9 and 3.3 times respectively in DHF compared to DF patients while aldolase was up-regulated 2.2 times in DF compared to DHF patients. Alpha tubulin and thioredoxin peroxidase have the potential to be utilized as biomarkers for DHF.